Investigating the performance of Hadoop and Spark platforms on machine learning algorithms - Mostafaeipour, Ali; Jahangard Rafsanjani, Amir; Ahmadi, Mohammad; Arockia Dhanraj, Joshuva (The Journal of supercomputing, 2021)
One of the most challenging issues in the big data research area is the inability to process a large volume of information in a reasonable time. Hadoop and Spark are two frameworks for distributed data processing. Hadoop is a very popular and general platform for big data processing. Because of the in-memory programming model, Spark as an open-source framework is suitable for processing iterative algorithms. In this paper, Hadoop and Spark frameworks, the big data processing platforms, are evaluated and compared in terms of runtime, memory and network usage, and central processor efficiency. Hence, the K-nearest neighbor (KNN) algorithm is implemented on datasets with different sizes within both Hadoop and Spark frameworks. The results show that the runtime of the KNN algorithm implemented on Spark is 4 to 4.5 times faster than Hadoop. Evaluations show that Hadoop uses more sources, including central processor and network. It is concluded that the CPU in Spark is more effective than Hadoop. On the other hand, the memory usage in Hadoop is less than Spark.